2013
DOI: 10.1371/journal.pone.0056717
|View full text |Cite
|
Sign up to set email alerts
|

Male Songbird Indicates Body Size with Low-Pitched Advertising Songs

Abstract: Body size is a key sexually selected trait in many animal species. If size imposes a physical limit on the production of loud low-frequency sounds, then low-pitched vocalisations could act as reliable signals of body size. However, the central prediction of this hypothesis – that the pitch of vocalisations decreases with size among competing individuals – has limited support in songbirds. One reason could be that only the lowest-frequency components of vocalisations are constrained, and this may go unnoticed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 40 publications
3
46
1
Order By: Relevance
“…Specifically, larger and heavier individuals (regardless of sex) produced calls at higher frequencies (maximum frequencies and bandwidths) than smaller ones, similar to what was found by Miyazaki and Waas (2003b). In many species, the frequency of vocalizations is correlated negatively with body size (Reby and McComb 2003, Hall et al 2013, Linhart and Fuchs 2015, Favaro et al 2017. However, such a relationship is not…”
Section: Discussionsupporting
confidence: 62%
“…Specifically, larger and heavier individuals (regardless of sex) produced calls at higher frequencies (maximum frequencies and bandwidths) than smaller ones, similar to what was found by Miyazaki and Waas (2003b). In many species, the frequency of vocalizations is correlated negatively with body size (Reby and McComb 2003, Hall et al 2013, Linhart and Fuchs 2015, Favaro et al 2017. However, such a relationship is not…”
Section: Discussionsupporting
confidence: 62%
“…The differences we see between the sexes in pitch may instead be due to differences in body size. Scaling of pitch with body size is an honesty-enforcing constraint seen across taxa (Fletcher, 2004;Hall, Kingma, & Peters, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We measured tarsus length (± 0.1 mm) 3 times at each capture, and used the average length as an indicator of body size. We used tarsus length as our measure of body size for the following three reasons: (1) it is observed to predict male quality and female choice in some birds (Kempenaers et al 1992;Møller & Ninni 1998;Hall et al 2013); (2) it has an observed relationship with call frequency (Price et al 2006;Brumm 2009;Geberzahn et al 2009;Linhart & Fuchs 2015); and (3) it is constant in adults.…”
Section: Body Size Measurementsmentioning
confidence: 99%
“…Therefore, birdsong, as a sexually selected multidimensional signal, can reveal singer information to some extent. It is well known that advertising songs can indicate body size (Hall et al 2013;Price & Crawford 2013). In many studies, all song characteristics reveal signaler quality through traits such as repertoire size (Soma & Garamszegi 2011;Hesler et al 2012;Kagawa & Soma 2013), song timing (Poesel et al 2006), song amplitude (Brumm 2009;Schuchmann & Siemers 2010), song frequency, song bandwidth or song rate (Potvin 2013;Linhart & Fuchs 2015;Mason & Burns 2015).…”
Section: Introductionmentioning
confidence: 99%